An accessory tongue in a child: A clinical case. Issue 6 (December 2021) - Ohara, Kenzo; Kanaya, Takeshi; Harabuchi, Yasuaki
Abstract: A 20-month-old male patient presented with a tumor on his tongue. The tumor was detected at birth with an initial size of 5 mm; thereafter, it gradually grew larger. The patient had no symptoms, but he frequently touched the tumor, as he grew older. The authors performed a tumor resection under general anesthesia, and the histopathological diagnosis confirmed that it was an accessory tongue, with the same components as that of a normal tongue. An accessory tongue regularly grows bigger as a patient grows older, resulting in dysphagia and articulation disorder. Younger patients should get accessory tongues surgically resected as soon as they are old enough to receive general anesthesia.